ESTUDO DO CAPM CONDICIONAL NO MERCADO ACIONÁRIO BRASILEIRO UTILIZANDO O MODELO DESENVOLVIDO POR JAGANNATHAN E WANG (1996) - CARASSINI, RONALDI (2017)
Asset pricing models, such as the Capital Asset Pricing Model (CAPM), are still widely discussed within the finance area, including in the scientific community as well. These models are used theoretically and practically in the area of investments to predict the risk and return of securities and portfolios, as well as in corporate finance, to analyze the viability of investments. Despite the discussions on the subject, there is still no unanimity on what rate of return should be taken at the time of the investment option. Considering these discussions about the ideal model, the objective of this work is to analyze if the application of the conditional CAPM model is valid to explain the returns of the Brazilian stock market. To answer this question, we will use the model developed by Jagannathan and Wang (1996), which introduced the possibility that betas and risk premium vary over time. For the application of this model in the Brazilian market, 40 stocks with the highest liquidity index of the Brazilian market were selected, divided into 5 (five) portfolios, each portfolio containing 8 shares, during the period from 2008 to 2016. The empirical results of this study suggest that the betas model and the risk premium varying over time can, with some adaptations, satisfactorily explain the cross-sectional variation of the portfolio returns analysed in this research. This study intends contribute to the area of finance and also, to the literature of asset pricing.